Social Prospects for Provocative Advertising ("Journal "U". Economy. Management. Finance.", 2020)
The problems of the social significance of provocative advertising are extremely relevant in the modern world, because due to information overload, ordinary types of advertising are no longer able to attract human attention. In this regard, the study carried out a review of the essence of provocative advertising and determined its influence on the minds of consumers. Attention is focused on advertising development trends along with the progression of society, which, in turn, is accompanied by an increase in tolerance among the population and recognition of human rights and freedoms as truly the highest value. The results of a study on the attitude of people to the use of various provocative topics in advertising are presented and conclusions are drawn that in the modern world advertising of this type plays a huge role both for the sale of goods and for increasing the level of tolerance among society.
Keywords: provocative advertising; marketing; society; tolerance; social progress